Dealing with multi-perspectivity in real-world laboratories. Experiences from the Transdisciplinary Research Project Urban Transformation Laboratories. - Engels, Anita; Walz, Kerstin (Oekom, 2018)
Real-world laboratories bring together stakeholders from research and outside academia in sustainability experimentation. However, different perspectives of partners and inherent goal conflicts often inhibit collaboration. We present strategies how multi-perspectivity can be channeled into synergies instead of unsurmountable conflicts. The project Urban Transformation Laboratories in Lokstedt (Hamburg) seeks to identify novel ways to combine local climate mitigation with urban planning, with a particular focus on the perspectives of local citizens. It serves as an example of transdisciplinary collaboration between two university partners and two local authorities, practice partners, and citizens. This Design Report focuses on strategies to address the challenges posed by multi-perspectivity among these different project stakeholders. We assume that building and maintaining trustful relations requires a careful balance of multiple perspectives, and that working with differences instead of forcing all partners to accept a unified perspective is the key to a successful collaboration. Finally, we briefly discuss the lessons we have learned so far on dealing with multi-perspectivity and the modifications we have introduced to our design.
Keywords: Nachhaltige Entwicklung; Klimaanpassung; Partizipation; Nachhaltige Stadtentwicklung; Nachhaltige Mobilität; Smart City; Wissenstransfer; Reallabor; Projektbericht; Transdisziplinarität